Natural fibre composites with furanic thermoset resins. Comparison between polyfurfuryl alcohol and humins from sugar conversion - Sangregorio, Anna; Muralidhara, Anitha; Guigo, Nathanael; Marlair, Guy; de Jong, Ed; Sbirrazzuoli, Nicolas (Composites. Part C, Open access, 2021)
3•Humins can be employed as a sustainable matrix for combination with jute fibres.3•Processing humins with jute needs shorter time compared to polyfurfuryl alcohol.3•Jute fibres mat becomes more hydrophobic after impregnation with humins.3•Impregnation with humins does not increase the fire hazard of the jute composite. Industrial humins from biorefining process of sugars were used as reactive thermoset matrix for the preparation of humins-jute fibre composites. This material was investigated and benchmarked with jute composites prepared with polyfurfurylalcohol (PFA), a well-known biobased thermosetting resin The Dynamic Mechanical Analyses (DMA) showed glass transition temperature (Tg) associated to the relaxation of the cross-linked humins’ chains at 75 °C similar to the Tg of PFA. The two types of composites revealed tensile properties in the same range and both materials demonstrated very low water uptake and good dimensional stability after immersion in liquid water. Such higher hydrophobicity compared to raw jute mat is the consequence of the good interfacial interaction of both furanic matrix with the jute fibres in agreement with SEM observations. Fire performance of materials was also investigated, demonstrating that the fire hazard of composites was not increased by the presence of furanic matrix. Interestingly, humins composites were slightly better than PFA composites for both the thermal and fire-induced toxicity threats. This study demonstrated the possibility of using industrial humins instead of PFA as a thermoset-like resin for the next generation of biobased composites. [Display omitted]